Estimation of Groundwater Recharge of the Holocen Aquifer from Rainfall by RIB Method for Hưng Yên Province - Rỡi, Nguyễn Đức (VNU Journal of Science: Earth and Environmental Sciences; Vol 30 No 4, 2014)
Abstract: Estimation of groundwater recharge from rainfall is a key factor for determining groundwater resources in water development and management. The paper presents application of rainfall infiltration breakthrough (RIB) model method for groundwater Holocene aquifer recharge estimation for Hưng Yên province in the Red RiverDelta,Vietnam. Although monitoring Holocene aquifer water level (WL) data are from different hydrogelogical either nearly naturally undisturbed or groundwater disturbed abstraction conditions, the relationship between the groundwater level fluctuation and cumulative rainfall departure is of a good match. The groundwater monitoring wells of the national monitoring network have been used are QT119, QT129 and QT130. The fractions of cumulative rainfall departure are from 13% for monitoring well QT119, and 12%-16% for wells QT129 and QT130. For the basic case of specifice yield of 0.1, the rainfall recharge rates are from 427mm (34.1% of mean annual rainfall) in the monitoring well QT119 area to 527mm (38.1% of mean annual rainfall) the area of monitoring wells QT129 and QT130 area. This recharge rates already include the evapotranspiration from the groundwater, which may be more or less than 50% of the total recharge rate and other possible discharge. Therefore, the obtained effective recharge is lightly greater then the range of 15%-20% of rainfall which is commonly used by theVietnamhydrogeologists. Keywords: Red River Delta, Cumulative Rainfall Departure (CRD), Rainfall Infiltration Breakthrough (RIB), Groundwater Recharge, Pearson Correlation, Spearman Correlation.